MtGSTF7, a TT19-like GST gene, is essential for accumulation of anthocyanins, but not proanthocyanins in Medicago truncatula. (16th March 2022) - Wang, Ruoruo; Lu, Nan; Liu, Chenggang; Dixon, Richard A; Wu, Qing; Mao, Yawen; Yang, Yating; Zheng, Xiaoling; He, Liangliang; Zhao, Baolin; Zhang, Fan; Yang, Shengchao; et al.
Abstract : MtGSTF7, a TT19-like GST gene, is activated by the transcription factor LAP1 to determine the accumulation of anthocyanins, but not proanthocyanins in Medicago truncatula . Abstract: Anthocyanins and proanthocyanins (PAs) are two end products of the flavonoid biosynthesis pathway. They are believed to be synthesized in the endoplasmic reticulum and then sequestered into the vacuole. In Arabidopsis thaliana, TRANSPARENT TESTA 19 (TT19) is necessary for both anthocyanin and PA accumulation. Here, we found that MtGSTF7, a homolog of AtTT19, is essential for anthocyanin accumulation but not required for PA accumulation in Medicago truncatula . MtGSTF7 was induced by the anthocyanin regulator LEGUME ANTHOCYANIN PRODUCTION 1 (LAP1), and its tissue expression pattern correlated with anthocyanin deposition in M. truncatula . Tnt1 -insertional mutants of MtGSTF7 lost anthocyanin accumulation in vegetative organs, and introducing a genomic fragment of MtGSTF7 could complement the mutant phenotypes. Additionally, the accumulation of anthocyanins induced by LAP1 was significantly reduced in mtgstf7 mutants. Yeast-one-hybridization and dual-luciferase reporter assays revealed that LAP1 could bind to the MtGSTF7 promoter to activate its expression. Ectopic expression of MtGSTF7 in tt19 mutants could rescue their anthocyanin deficiency, but not their PA defect. Furthermore, PA accumulation was not affected in the mtgstf7 mutants. Taken together, our results show that the mechanism of anthocyanin and PA accumulation in M. truncatula is different from that in A. thaliana, and provide a new target gene for engineering anthocyanins in plants.